2018
DOI: 10.1177/0309133318783144
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better understanding of climate and human impacts on late Holocene fire regimes in the Pacific Northwest, USA

Abstract: In order to fully appreciate the role that fire, both natural and anthropogenic, had in shaping pre-Euro-American settlement landscapes in the Pacific Northwest (PNW), it is necessary to develop a more robust method of evaluating paleofire reconstructions. Here we demonstrate an approach that includes the identification of charcoal morphotypes (i.e. visually distinct charcoal particles), and incorporates both paleoecological and archaeological data sets, to more specifically determine both the nature of past f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 118 publications
(180 reference statements)
0
25
0
Order By: Relevance
“…, Walsh et al. , ). This past fire suppression and exclusion can impact current fire severity and size, particularly in drier ecosystems with shorter fire return intervals (Hantson et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Walsh et al. , ). This past fire suppression and exclusion can impact current fire severity and size, particularly in drier ecosystems with shorter fire return intervals (Hantson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Frameworks in North America have broadened to consider the influence of humans in the evolution of natural ecosystems. For example, the use of fire by indigenous peoples, which has occurred for thousands of years in North America, is increasingly regarded as part of the natural disturbance regime under which many ecosystems in the Western United States have evolved [73,74]. Accordingly, particular ecological communities, including groves of large California black oaks (Quercus kelloggii) and Oregon white oaks (Quercus garryana), camas grounds (Camassia spp.…”
Section: Humans Are Part Of Most Natural Systemsmentioning
confidence: 99%
“…Finally, CharTool incorporates an optional charcoal fragment morphotype classification component for each charcoal fragment that is selected by the user. Several studies have suggested that combustion conditions and fuels consumed during a fire determine the morphology and structure of charred fragments (Courtney Mustaphi and Pisaric 2014; Enache and Cumming 2006;Jensen et al 2007;Walsh et al 2018). Thus, charcoal fragment morphology is increasing used as a metric for estimating fuel sources and intensities of landscape fires.…”
Section: Figurementioning
confidence: 99%